Brand Sepatu Compass dalam Masa Sulit: Analisis Penyebab dan Upaya Strategis untuk Keluar dari Krisis di Tahun 2024 - Victor Lucas, Ivan; Kresna Noer, Mochammad (Da'watuna: Journal of Communication and Islamic Broadcasting, 2026)
This study aims to analyze the causes of the crisis experienced by the Compass shoe brand in 2024 and identify effective recovery strategies. The background of this study focuses on various factors contributing to the brand's decline, including socio-cultural changes, technological developments, and increasingly fierce market competition. To achieve this objective, this study used a qualitative approach with in-depth interviews and document analysis. The collected data was analyzed using the GE McKinsey Matrix, which helps evaluate Compass's strategic position based on market attractiveness and business strengths. The results indicate that Compass's declining performance was influenced by rapidly changing consumer trends and the brand's inability to adapt to technological innovations and more effective marketing strategies. Based on the GE McKinsey Matrix analysis, the proposed recovery strategy involves increasing product innovation, adjusting marketing strategies, and improving internal management. The conclusions of this study highlight the importance of swift and focused action to overcome the crisis and provide practical recommendations for Compass management in facing future challenges.